Soft Fibrillar Materials : Fabrication and Applications. - Li, Jing Liang (Wiley, 2013)
The book covers the most important soft functional materials, including small molecule physical gels, polymer gels, and functional fibers, with respect both to the fundamentals and to development and engineering methods. It provides the reader with the necessary knowledge regarding the chemical and physical formation mechanisms of these materials, and demonstrates that one can rationally design and tune fibrillar networks so that the resulting materials exhibit desired functionalities. It also shows how materials from nature such as spider silk can be adapted for man-made applications and even.